TECHNOLOGY OF EXTRACTING HIGHVISCOSITY OILS FROM THE WELL - Bolibekova Shakhnoza Yarkulovna; Yakhshiyeva Kibriyo Oybekovna; Mansurov Aziz Abdikarimovich (Western European Studies, 2024)
The permeability of rocks in one layer can vary dramatically in its different zones or sections. Sometimes, when the general permeability of the formation is good, some wells are opened in the zones of low permeability, as a result of which oil and gas flow to it becomes worse
Keywords: permeability; rocks; opened; sections